A new species of Chasmogenus Sharp, 1882 and new records of Hydrophilidae (Coleoptera) from Northeastern Brazil - Alves, Tayná; Clarkson, Bruno; Lima, Lucas Ramos Costa (Zootaxa, 2020)
Chasmogenus cajuina sp. nov., a new species of the water scavenger beetle (Hydrophilidae: Acidocerinae) is described and illustrated, based on adult males, collected in the Lower Parnaíba River Basin, north of Piauí, Northeast Region of Brazil. In addition, Helochares (Sindolus) femoratus (Brullé, 1841) and Hydrobiomorpha spatula Bachmann, 1988 are recorded from Piauí State for the first time.